1994
DOI: 10.1002/aoc.590080318
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary toxicity of indium arsenide and arsenic selenide following repeated intratracheal instillations to the lungs of hamsters

Abstract: Chronic toxicity of indium arsenide (InAs) and arsenic selenide (As,Se,) was studied in male Syrian golden hamsters which received InAs or As,Se, particles, each containing a total dose of 7.5 mg of arsenic, by intratracheal instillations once a week for 15 weeks. As a control, hamsters were treated with the vehicle, phosphate buffer solution. During their total lifespan, the cumulative body weight gain of the hamsters in the InAs group was suppressed significantly compared with that in the control group, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
25
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 16 publications
5
25
1
Order By: Relevance
“…In our previous study, we confirmed the development of proteinosis-like lesions or localized hyperplastic lesions in the lungs of hamsters which had been induced by exposure to InAs particles [3][4][5] . In particular, alveolar or bronchiolar cell hyperplasia with squamous cell metaplasia, squamous cell hyperplasia or squamous cell metaplasia with keratinization were observed when 7.7 mg/kg of InAs was instilled intratracheally, twice a week for a total of 14 times 4) .…”
supporting
confidence: 78%
See 1 more Smart Citation
“…In our previous study, we confirmed the development of proteinosis-like lesions or localized hyperplastic lesions in the lungs of hamsters which had been induced by exposure to InAs particles [3][4][5] . In particular, alveolar or bronchiolar cell hyperplasia with squamous cell metaplasia, squamous cell hyperplasia or squamous cell metaplasia with keratinization were observed when 7.7 mg/kg of InAs was instilled intratracheally, twice a week for a total of 14 times 4) .…”
supporting
confidence: 78%
“…In particular, alveolar or bronchiolar cell hyperplasia with squamous cell metaplasia, squamous cell hyperplasia or squamous cell metaplasia with keratinization were observed when 7.7 mg/kg of InAs was instilled intratracheally, twice a week for a total of 14 times 4) . Accordingly, a further study was undertaken with only half the dose (4 mg/kg).…”
mentioning
confidence: 99%
“…Due to the increasing production of ITO, the potential health hazards of occupational or environmental exposure to this material have began to cause great concern. Since the mid 1990's, data have become available indicating that indium compounds can be toxic to animals [2][3][4][5][6][7][8][9][10][11][12] , although there is little information regarding the adverse health effects for workers exposed to indium compounds. In 2003, the first case of interstitial pneumonia caused by occupational exposure to ITO was reported 13) .…”
mentioning
confidence: 99%
“…From the mid-1990s, animal experiments have shown that the inhalation or intratracheal instillation of In compounds causes severe lung inflammation [1][2][3][4][5][6][7] and mild adverse reproductive effects [8][9][10] . Although the health effects of In on workers' respiratory and reproductive systems have been unclear to date, assessing the exposure-effect relationships in Inexposed workers is a serious concern, but no information is available on the exposure-effect relationships in workers.…”
mentioning
confidence: 99%